2012
DOI: 10.1080/0144929x.2011.638396
|View full text |Cite
|
Sign up to set email alerts
|

Collective activities in a technology-mediated medical team. An analysis of epidemiological alert management

Abstract: We conducted an exploratory study of a complex and dynamic medical activity, namely the collective management of an epidemiological alert situation. With a view to improving our knowledge of how this activity is managed, we set up simulated situations of epidemiological alerts. A multidisciplinary medical team was assisted by a decisionsupport system called ASTER and we recorded a set of systematised observations of human-human and humanmachine interactions. Participants were physicians belonging to the Depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, observational studies have found that synchronous communication accounts for the vast majority of humanhuman interactions in epidemiology work, with co-located communication taking up to 42% of the time spent on the task [10]. In order to address this issue, the work described here builds on the nu-case system, and extends its visualization tools [5] by allowing information to be shared on large displays at meetings, while preserving its key features for supporting the tasks performed by individual analysts using their small displays.…”
Section: Analysis Of Disease Spreadmentioning
confidence: 99%
See 1 more Smart Citation
“…However, observational studies have found that synchronous communication accounts for the vast majority of humanhuman interactions in epidemiology work, with co-located communication taking up to 42% of the time spent on the task [10]. In order to address this issue, the work described here builds on the nu-case system, and extends its visualization tools [5] by allowing information to be shared on large displays at meetings, while preserving its key features for supporting the tasks performed by individual analysts using their small displays.…”
Section: Analysis Of Disease Spreadmentioning
confidence: 99%
“…In epidemiology settings, such tasks include surveillance, risk assessment, early warning of outbreaks, planning of preventive interventions, countermeasures, medical examinations and others [10]. The use of maps to explain and predict patterns of disease spread and to support epidemiological reasoning is well-established in medical research [14].…”
Section: Analysis Of Disease Spreadmentioning
confidence: 99%
“…In particular, the activities performed by the healthcare providers in the context of disease surveillance and patient care in the geographical area on which our research has focused can be characterised along the lines of two interrelated group work processes, namely, cooperation and collaboration. Gaudin et al (2012), drawing on a conceptualisation elaborated by Rogalski (1994) and others, consider cooperation to occur when the team members involved perform different activities but pursue a common goal. Collaboration, on the other hand, occurs when team members not only pursue the same common goal, but also work on the same task together to achieve it.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Teams have been defined as groups of people who deal with different sources of information and perform a number of activities as an integrated unit to achieve a common goal (Gaudin et al 2012, Cooke 2004. Figure 2 presents a diagrammatic overview of the interactions between actors involved in disease surveillance and patient care in Southwestern Amazonia as an instantiation of the scheme described in Gaudin et al (2012).…”
Section: Team Collaboration and Cooperationmentioning
confidence: 99%
See 1 more Smart Citation